Data series of hydrographic variables, potentially toxic phytoplankton and marine biotoxins in bivalves from open waters off the Basque coast (SE Bay of Biscay)Mendeley Data - Oihana Solaun; Izaskun Zorita; Marta Revilla; Manuel González; Joana Larreta; Luis Cuesta; Almudena Fontán; Luis Ferrer; Yolanda Sagarminaga; Aitor Laza-Martínez; Carolina Assadi; José Germán Rodríguez (Data in Brief)
Marine biotoxins produced by some potentially toxic phytoplankton species can accumulate in shellfish, posing a threat to human health through consumption. This dataset was generated from monitoring the open waters of the shellfish production area off the Basque coast (southeastern Bay of Biscay) from December 2013 to December 2023. It includes data on the abundance of potentially toxic phytoplankton, the levels of marine biotoxins in bivalves, and various hydrographic variables. Not all the variables were measured throughout the whole monitoring period and the sampling frequency varied. Generally, surveys were conducted monthly or biweekly, with the exception of a seven-month gap between September 2015 and March 2016. Biotoxin analyses on bivalves involved Amnesic Shellfish Poisoning (ASP) and Paralytic Shellfish Poisoning (PSP) toxins, as well as, lipophilic toxins (Okadaic Acid (OA), Dinophysistoxins (DTXs), Pectenotoxins (PTXs), Yessotoxins (YTXs) and Azaspiracids (AZAs)). The identification and counting of potentially toxic algal cells were performed using the Utermöhl method with light microscopy. Continuous vertical profiles of hydrographic variables (temperature, salinity, light transmission, photosynthetically active radiation, chlorophyll “a” and dissolved oxygen) were measured in situ using Sea-Bird SBE-25 and 25plus CTD instruments. As a whole, this dataset may be useful for: (i) assessing temporal trends of hydrographic variables, potentially toxic phytoplankton, and marine biotoxins in bivalves from offshore waters of the Basque coast, (ii) comparing local marine biotoxin levels with established safety limits for human consumption, or levels found in other biogeographical areas, and (iii) supporting the management of shellfish production in the Basque coastal waters and similar biogeographic areas from an integrated perspective.